Prevalence of Infective Endocarditis among Patients with Staphylococcus aureus Bacteraemia and Bone and Joint Infections - Matthaios Papadimitriou-Olivgeris; Benoit Guery; Pierre Monney; Laurence Senn; Sylvain Steinmetz; Noémie Boillat-Blanco (Microorganisms, 2024)
We aimed to evaluate the occurrence of infective endocarditis (IE) among patients with bone and joint infections (BJIs) and Staphylococcus aureus bacteraemia. This observational study was conducted at Lausanne University Hospital, Switzerland, from 2014 to 2023, and included episodes involving BJI, S. aureus bacteraemia, and cardiac imaging studies. The endocarditis team defined IE. Among the 384 included episodes, 289 (75%) involved native BJI (NBJI; 118 septic arthritis, 105 acute vertebral or non-vertebral osteomyelitis, 101 chronic osteitis), and 112 (29%) involved orthopedic implant-associated infection (OIAI; 78 prosthetic joint infection and 35 osteosynthesis/spondylodesis infection). Fifty-one episodes involved two or more types of BJI, with 17 episodes exhibiting both NBJI and OIAI. IE was diagnosed in 102 (27%) episodes. IE prevalence was 31% among patients with NBJI and 13% among patients with OIAI (p < 0.001). The study revealed a high prevalence of IE among S. aureus bacteraemic patients with NBJI, with notably lower prevalence among those with OIAI.